Genetic Testing between Private and Public Interests: Some Legal and Ethical Reflections - Sándor, Judit (Frontiers in Public Health, 2018)
In Europe there is a wide variety of genetic tests that various private companies offer to patients or to consumers. More and more people have become curious about their genetic predisposition and susceptibility. Most public health care systems, however, are not adequately prepared for responding to these new demands and to the results of these genetic tests as quite often there is no available therapy for the identified genetic condition. This discrepancy between the newly emerging expectations and the insufficient responses contributes to a further rift between the public and private sectors of health care. Individual genetic test results may also trigger the need for personalized medicine and may open up a competition between the two fields in offering further genetic tests and medical exams. Pro-active patients may need a different kind of information on genetic tests and their implications. In this context, how should the public health system deal with the challenges of private testing? Will private genetic testing transform health care from a solidarity-based system to an individualistic one? In this paper I would like to explore the emerging legal and ethical issues related to genetic testing and the relevant legal framework that has developed so far. At the end of the paper I would like to examine the possibility of further legal development.